1986
DOI: 10.1139/m86-038
|View full text |Cite
|
Sign up to set email alerts
|

Germination of Bacillus cereus spores induced by purine ribosides and their analogs: effects of modification of base and sugar moieties of purine nucleosides on germination-inducing activity

Abstract: Purine riboside and some of its analogs were tested for their ability to induce germination of Bacillus cereus T spores. Hypoxanthine and adenine showed no germination-inducing activity either in the present or absence of D-ribose or its phosphorylated derivatives. Purine riboside and 18 analogs with modified purine base were all able to induce germination of the spores to various extents. In contrast to this, the requirement for the sugar moiety in the purine riboside appeared to be more stringent. Only those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 6 publications
4
10
0
Order By: Relevance
“…However, only changes in the purine ring are tolerated. These results are consistent with previous work that showed the importance of the sugar moiety in nucleoside recognition (Preston & Douthit, 1988;Senesi et al, 1991;Shibata et al, 1986;Yousten, 1975).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, only changes in the purine ring are tolerated. These results are consistent with previous work that showed the importance of the sugar moiety in nucleoside recognition (Preston & Douthit, 1988;Senesi et al, 1991;Shibata et al, 1986;Yousten, 1975).…”
Section: Discussionsupporting
confidence: 93%
“…The nucleoside/alanine germination pathway can be activated by a larger variety of nucleoside analogues in the presence of L-alanine (Abel-Santos & Dodatko, 2007). These results are consistent with previous spore germination experiments in B. cereus NCIB 8122 and T strains (Preston & Douthit, 1988;Senesi et al, 1991;Shibata et al, 1986;Yousten, 1975). B. anthracis, a species closely related to B. cereus, can also germinate using this pathway (Ireland & Hanna, 2002;Weiner et al, 2003).…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…These results are consistent with previous spore germination experiments in B. cereus NCIB 8122 and T strains (Preston and Douthit, 1988;Senesi et al, 1991;Shibata et al, 1986;Yousten, 1975).…”
Section: Bacillus Cereus Ger Receptorssupporting
confidence: 93%
“…Analysis of structurally diverse nucleosides used as cogerminants with L-alanine suggested that, in the nucleoside/alanine pathway, germination-inducing activity is governed by the structural properties of the sugar rather than the base moieties of the nucleoside (Shibata et al, 1986). These results are consistent with previous spore germination experiments in B. cereus NCIB 8122 and T strains (Preston and Douthit, 1988;Senesi et al, 1991;Shibata et al, 1986;Yousten, 1975).…”
Section: Bacillus Cereus Ger Receptorssupporting
confidence: 88%